Assessment of procrastination in providing nursing care among Iranian nursing staff - Mohadese Babaie; Azam Shirinabadi Farahani; Manijeh Nourian; Mahdi Hosseini; Arman Mohammadi (BMC, 2022)
Abstract Aim This study aimed to investigate procrastination in nursing care providing. Design This descriptive cross-sectional study was carried out on 125 nurses in ICUs, PICUs, NICUs, and surgery wards, who were selected by census sampling in Iran. Methods The data were collected using the Procrastination Scale, which consisted of 25 items relating to 3 factors. Data were analyzed using statistics, Chi-square, Friedman test, analysis of variance, and Kolmogorov-Smirnov tests. Results Overall, 37% of the participants showed very high or high procrastination. Most of the procrastination was observed in the "Task aversion" (44.2%). ANOVA indicated that the mean total procrastination score had a significant relationship with age (p = 0.013), work experience (p = 0.006), and marital status (p = 0.02). Nurses with permanent employment (p = 0.014) and lower education (p = 0.009) and women (p = 0.023) were much more likely to procrastinate the provision of care. Conclusion It is recommended to adopt appropriate management strategies and take adequate measures to reduce procrastination, considering the existence of procrastination among nurses and its adverse impact on the quality of care.